Multigrade Teaching Challenges and Opportunities - Sangai, Sandhya (JOURNAL OF INDIAN EDUCATION, 2019)
We often come across some primary school, especially in rural and remotely located areas, staffed with one or two teachers. In sparsely populated habitations, due to thin size of enrollemnt, the number of teachers allotted for the schools is less than the number of grades. This requires action on the part of the available teachers to combine several grades. Primary schools with multigrade teaching are acknowledged for their constraints in several research studies. However, pedagogical concerns, skills and methods required for multigrade teaching situations have different rationale from common situations of monograde teaching. This paper discusses some strategies for organising teaching-learning in a multigrade context, how to covert multigrade challenges into opportunities and how the teachers should be oriented to teach multigrade classrooms.